Effect of cholinergic and adrenergic stimulation of the subfornical organ on water intake - Menani, José Vanderlei [UNESP]; Saad, William A. [UNESP]; Camargo, L. A A [UNESP]; Antunes-Rodrigues, J. [UNESP]; Covian, M. R. [UNESP] (My University, 1984)
Cholinergic and adrenergic agonists and antagonists were injected directly into the subfornical organ (SFO), via implanted cannulae, and the volume of water ingested was recorded over a period of 1 hour after injection. Application of 2 nmol carbachol caused intense water intake in 100% of the animals (8.78±0.61 ml), with a very short intake latency. When the 2 nmol carbachol dose was preceded by increased doses of atropine, a progressive reduction in water intake was observed, with complete blockage of the thirst-inducing response to carbachol at the 20 nmol dose level with atropine. Followed by several doses of hexamethonium, the water intake caused by application of 2 nmol carbachol was reduced, although the response was not totally blocked. Injection of 80 nmol of nicotine had a significant thirst-inducing inducing effect in 50% of the animals studied (1.06±0.18 ml) and increase in water intake was further reduced by application of increased doses of hexamethonium. Raising the dose levels of noradrenaline into th SFO caused an increase in water intake although to a lesser degree than was observed after carbachol injection. When the 40 nmol dose of noradrenaline was preceded by increased doses of propranolol (5 to 40 nmol), there was a gradual reduction in water intake, with total blockage at the 40 nmol dose. Application of phentolamine in doses of 10 to 80 nmol caused no reduction in water intake after 40 nmol of noradrenaline. Application of isoproterenol at doses from 20 to 160 nmol into the SFO caused a dosedependent increase in water intake which was blocked by previous applications of propranolol. These results support the hypothesis that the water intake caused by chemical stimulation of the SFO is mainly due to muscarinic cholinergic receptors, although the influence of nicotinic receptors or participation of adrenergic mediation should not be ruled out. © 1984.
Keywords: Adrenergic mediation; Cholinergic mediation; Subfornical organ; Water intake; adrenergic receptor; atropine; carbachol; cholinergic receptor; hexamethonium; isoprenaline; nicotine; noradrenalin; phentolamine; phentolamine mesylate; propranolol; animal experiment; central nervous system; drinking; drug efficacy; fluid intake; intracerebral drug administration; nonhuman; rat; subfornical organ; Animals; Atropine; Carbachol; Dose-Response Relationship, Drug; Drinking Behavior; Hexamethonium Compounds; Male; Neurosecretory Systems; Nicotine; Norepinephrine; Parasympathetic Nervous System; Phentolamine; Propranolol; Rats; Subfornical Organ; Sympathetic Nervous System; Animalia